Environmental ergonomics : the ergonomics of human comfort, health, and performance in the thermal environment - Tochihara, Yutaka; Ohnaka, Tadakatsu (Elsevier ergonomics book series, 2005)
Environmental Ergonomics addresses the problems of maintaining human comfort, activity and health in stressful environments. Its subject areas include thermal environments, illumination, noise and hypo- and hyperbaric environments. The book concentrates fundamentally on the way the thermal environment has affected human comfort, health and performance from the age of cave-dwellings to our age of skyscrapers. This book contains only papers selected from the 10th ICEE held in Japan 23-27 September 2002. The ICEE has been held biannually since 1982, and has firmly established itself as the worlds most distinguished conference in its field, offering the ideal forum for research scientists, medical doctors, engineers, administrators, technicians, healthcare professionals and students to share their work and ideas. Selected papers from the 10th International Conference on Environmental Ergonomics held in Japan, 23-27 September 2002. They have been revised and peer-reviewed. Papers included in this text have been widely recognised as the catalyst for the recent advances witnessed in Environmental Ergonomics in Asia. They strike a balance between academia and industries' views on environmental ergonomics. Add this volume to your copy of the Elsevier Ergonomics Book Series.